The Tale of the Roman Theater of Philadelphia, Amman. Representative and experiential methodology of the theatrical space - Giuseppe Amoruso (Disegnare con)
The project aims to present the 3D reconstruction of the Roman Theater of Amman, the ancient Philadelphia of the Palestinian Decapolis, through rigorous representative models. The outcomes will be part of a future exhibition providing site-specific installations and user experience artifacts based on digital interaction and tactile models. The paper illustrates the multidisciplinary approach associated with using 3D virtual reconstruction and game engine tools to reflect on the practice of representing ancient monuments and digital museology. Travelers of the 18th and 19th centuries drafted the fascination of discovery as an experience in their notebooks. At the same time, their written records could address contemporary visitors to an extensive cultural knowledge of places and buildings, the historia of Philadelphia. Investigations are shifting scientific models towards a dynamic cultural experience representative of cultural heritage, including intangible heritage, stories, and new technological paradigms, increasingly rapidly making it possible to duplicate art and heritage. This shift is pinpointing the role of representation for cultural studies and humanities, experimenting with practices and tools to drill methodologies, and producing models for interaction design, socialization, gaming, and museum experience. DOI: https://doi.org/10.20365/disegnarecon.31.2023.15